Báo cáo tổng kết thực hiện Pháp lệnh Bảo vệ công trình quốc phòng và khu quân sự (1994 - 2021) - Bộ Quốc phòng (2022)
Toàn văn Báo cáo tổng kết thực hiện Pháp lệnh Bảo vệ công trình quốc phòng và khu quân sự (1994 - 2021).